Interaction of L-ascorbic acid and α-tocopherol in alleviating 1, 4-benzoquinone, a metabolite of benzene induced genotoxicity in male Wistar rats. Issue 1 (31st December 2023) - Mishra, Ritu; Dutta, Karabi; Bharali, Manuj Kr.
ABSTRACT: The present study investigated the possible protective effects of L-ascorbic acid and α-tocopherol on 1, 4-benzoquinone (BQ) induced chromosomal aberrations, DNA damage and lipid peroxidation in male Wistar rats. Animals were randomly divided into five groups. The control group received normal feed and clean drinking water. The second group received single dose of BQ (3mgkg −1, ip), the third and fourth group received L-ascorbic acid (100 mgkg −1 ) and α-tocopherol (100mgkg −1 ) orally along with BQ. The fifth group received a combined dose of L-ascorbic acid (100mgkg −1 ) and α-tocopherol (100mgkg −1 ) with BQ. BQ caused significant increase in the percentage of chromosomal aberration, formation of micronuclei, DNA damage in peripheral lymphocytes and increased MDA content. However, the cotreatment with either L-ascorbic acid or α-tocopherol resulted in significant decline in the micronuclei formation, chromosomal abnormalities, DNA damage and MDA level, and restoration of mitotic indices in BQ treated animals. The protective effects of L-ascorbic acid and α-Tocopherol were found to be significantly enhanced in combined dosed treated group. The result of the present study indicated that combined supplementation of both water-soluble and lipid-soluble vitamins was more efficient at reversing the genotoxic changes induced by BQ in the bone marrow cells of Wistar rats.